Loss of Sirt2 increases and prolongs a caerulein-induced pancreatitis permissive phenotype and induces spontaneous oncogenic Kras mutations in mice. Issue 1 (December 2018) - Quan, Songhua; Principe, Daniel; Dean, Angela; Park, Seong-Hoon; Grippo, Paul; Gius, David; Horikoshi, Nobuo
Abstract Mice lackingSirt2 spontaneously develop tumors in multiple organs, as well as when expressed in combination with oncogenicKras G12D, leading to pancreatic tumors. Here, we report that after caerulein-induced pancreatitis, Sirt2 -deficient mice exhibited an increased inflammatory phenotype and delayed pancreatic tissue recovery. Seven days post injury, the pancreas ofSirt2 −/− mice display active inflammation, whereas wild-type mice had mostly recovered. In addition, the pancreas from theSirt2 −/− mice exhibited extensive tissue fibrosis, which was still present at six weeks after exposure. The mice lackingSirt2 also demonstrated an enhanced whole body pro-inflammatory phenotype that was most obvious with increasing age. Importantly, an accumulation of a cell population with spontaneous cancerousKras G12D mutations was observed in theSirt2 −/− mice that is enhanced in the recovering pancreas after exposure to caerulein. Finally, transcriptome analysis of the pancreas of theSirt2 −/− mice exhibited a pro-inflammatory genomic signature. These results suggest that loss ofSirt2, as well as increased age, enhanced the immune response to pancreatic injury and induced an inflammatory phenotype permissive for the accumulation of cells carrying oncogenicKras mutations.